Upaya Meningkatkan Hasil Belajar Siswa melalui Strategi Reading Guide pada Pembelajaran Akidah Akhlak di Kelas IV Madrasah Ibtidaiyah Negeri 1 Serdang Bedagai - Mutia Mauliddiya; Mardianto Mardianto; Nirwana Anas (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to determine: (1) the learning outcomes before using the Reading Guide learning strategy in the Islamic Theology and Ethics (Akidah Akhlak) subject on the topic of Asmaul Husna in class 4A of MIN 1 Serdang Bedagai; (2) the learning outcomes after using the Reading Guide strategy in the same subject and class; and (3) the implementation of the Reading Guide strategy in improving students’ learning outcomes. This research is a Classroom Action Research (CAR) involving 27 students from class 4A as the research subjects. The findings indicate that prior to the implementation of the strategy, students’ average score was 58.9%, with only 26% (7 students) achieving the minimum mastery criteria. After applying the Reading Guide strategy in Cycle I, the average score increased to 67.03%, with 59% (16 students) achieving mastery. In Cycle II, the average score further increased to 83.37%, with 100% (27 students) meeting the mastery criteria. Therefore, it can be concluded that the Reading Guide strategy effectively improves students’ learning outcomes in the Islamic Theology and Ethics subject on the topic of Asmaul Husna in class 4A of MIN 1 Serdang Bedagai for the academic year 2022–2023.